PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Teysha Hiramatsu (Jurnal Akuntansi Kompetif, 2026)
This study aims to examine the effect of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and financial performance on firm value. Firm value is measured using Tobin's Q, while GCG, CSR, and financial performance are proxied by the Corporate Governance Perception Index, Global Reporting Initiative disclosure index, and Return on Assets, respectively. The population in this study comprises finance sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. By employing a purposive sampling method, the data were analyzed using multiple linear regression analysis. The results of the simultaneous test indicate that GCG, CSR, and financial performance collectively exert a significant effect on firm value. Furthermore, the partial test results reveal that GCG has no significant effect on firm value. Interestingly, CSR demonstrates a significant but negative effect on firm value. Conversely, financial performance exhibits a positive and significant impact on firm value, indicating that investors heavily rely on profitability as a primary signal for investment returns. Keywords: Good Corporate Governance, Corporate Social Responsibility, Financial Performance, Firm Value